PENGEMBANGAN PENDIDIKAN KREATIF DENGAN MEMANFAATKAN PEMBELAJARAN DIGITAL - Indahsari, Haryani; Sari, Yeni Anita (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstract— Digital learning system that is triggered by the intensity of the use of information technology is growing rapidly and substantially large where the emergence of various forms of digital teaching materials, digital-based learning scenarios, assessment of learning outcomes and so on. The ability and skills to use ICT in quality learning, the development of digital learning materials that can be utilized by the wider community to improve competence, as well as digital evaluation of learning. Digital learning can also be interpreted as a learning process carried out through a network (computer network), usually via the internet or intranet. With internet facilities, digital learning does not depend on teachers, because access to information (knowledge) is more extensive and complete, so learners can learn anytime and anywhere. One of digital learning is E-learning learning. Electronic learning (E-learning) is evidence of the extraordinary progress of human civilization. The benefits of E-Learning to the world of education are through electronic learning media (E-Learning) students will become more sensitive to technology. Keywords— Digital Learning, Education, E-learning Abstrak—Sistem pembelajaran digital yang dipicu oleh intensitas penggunaan teknologi informasi ini berkembang cepat dan luas secara substansial dimana munculnya beragam bentuk bahan ajar digital, skenario pembelajaran berbasis digital, penilaian hasil belajar dan sebagainya. Kemampuan dan ketrampilan untuk menggunakan TIK dalam pembelajaran yang berkualitas, pengembangan bahan-bahan pembelajaran digital yang dapat dimanfaatkan oleh masyarakat luas untuk meningkatkan kompetensi, serta evaluasi belajar secara digital. Pembelajaran Digital dapat pula diartikan sebagai sebuah proses pembelajaran yang dilakukan melalui network (jaringan komputer), biasanya lewat internet atau intranet. Dengan fasilitas internet, pembelajaran digital tidak tergantung pada pengajar, karena akses informasi (knowledge) lebih luas dan lengkap, sehingga pembelajar dapat belajar kapan saja dan dimana saja. Salah satu pembelajaran digital adalah pembelajaran E-learning. Pembelajaran elektronik (E-learning) adalah bukti kemajuan luar biasa dari peradaban manusia. Manfaat E-Learning bagi dunia pendidikan ialah melalui media pembelajaran elektronik (E-Learning) siswa akan menjadi lebih pekah terhadap teknologi. Kata Kunci— Pembelajaran Digital, Pendidikan, E-learning